Whither Stakeholder Theory? A Guide for the Perplexed Revisited - Hasnas, John (2013)
The nature of stakeholder theory and its fundamental normative prescriptions are the subject of much confusion and academic debate. This article attempts to provide an account of both the fundamental normative implications of stakeholder theory and the theory’s range of application that both stakeholder advocates and critics can agree upon. Using exclusively the language of leading stakeholder theorists, the article identifies the essential prescriptions of the theory and the type of organizations to which stakeholder theory applies in the hope of facilitating effective discussion and evaluation of the normative dimension of stakeholder theory.
Keywords: Labor unions; Organizational Ethics; Agency Theory; Stakeholder Theory